2018
DOI: 10.1111/jmft.12362
|View full text |Cite
|
Sign up to set email alerts
|

Black–White Marriages: The Moderating Role of Openness on Experience of Couple Discrimination and Marital Satisfaction

Abstract: This study examined how open communication between spouses may buffer against discrimination experienced by Black–White couples. Results from 178 couples analyzed using a combination of common‐fate and actor–partner interdependence models, indicated that for Black partners, marital satisfaction was not contingent on the level of openness when experiences of couple discrimination were low. When experiences of couple discrimination were high, levels of marital satisfaction were maintained among partners who repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Conversely, maladaptive strategies may exacerbate the situation byleading to conflict and harm to the victims and those close to them. Being in a minority and feeling rejected by society can often cause stress and tension between romantic partners (Baptist et al, 2018;Genc & Baptist, 2020;Genc & Su, 2021).…”
Section: Effects Of Discrimination On Intimate Relationshipsmentioning
confidence: 99%
See 3 more Smart Citations
“…Conversely, maladaptive strategies may exacerbate the situation byleading to conflict and harm to the victims and those close to them. Being in a minority and feeling rejected by society can often cause stress and tension between romantic partners (Baptist et al, 2018;Genc & Baptist, 2020;Genc & Su, 2021).…”
Section: Effects Of Discrimination On Intimate Relationshipsmentioning
confidence: 99%
“…On the other hand, these difficult experiences may strengthen intimate relationships through creating chances for closeness and support. Thus, the relationship may function better through increased commitment, stability, and satisfaction (Baptist et al, 2018;Genc & Su, 2021;Kamen, Burns, & Beach, 2011).…”
Section: Effects Of Discrimination On Intimate Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…When Lehmiller and Agnew ( 2006 ) explored the association between relationship marginalization and relationship investment and commitment, they found that being in a marginalized relationship (i.e., same-sex, interracial, or age-gap) was associated with lower levels of investments in relationships. Stigma as a result of relationship type has been related to lower levels of commitment, trust, love, and even relationship satisfaction (Baptist et al, 2019 ; Vazquez et al, 2019 ). There is evidence that not all individuals in interracial relationships are negatively impacted by stigma.…”
Section: Introductionmentioning
confidence: 99%